PERBANDINGAN TINGKAT KEBUGARAN JASMANI ANTARA SISWA YANG BERSEKOLAH DI DATARAN TINGGI DAN DATARAN RENDAH (STUDI PADA SELURUH SISWA KELAS VII SMPN 5 BATU DAN SMPN 7 KOTA MOJOKERTO) - DUL FAQOR, SAIFUD (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Sport is important for human to obtain fit and healthy life. In school environment, the health and physical fitness of the students are achieved through exercises and doing sports applied in physical education subject. This study aims to know (1) the difference in physical fitness between the students of junior high school located in mountainous area, i.e. the seventh graders of VII SMPN 5, and the one located in the coastal area, i.e. those of SMPN 7 kota Mojokerto; and (2) whose physical fitness is better between the two groups. This study used non-experimental design within descriptive quantitative approach, which did not manipulate any variable. The hypothesis testing was based on the results of data tabulation of the students’ physical fitness between the two groups, which were statistically organized and analyzed to test the hypothesis, the researcher used t-test. The calculation of the t-test shows that the t-value is 0.601, which is less than t-table (2,000) at the significance level of 5%. Therefore, Ha is rejected and Ho is accepted. It means that there is no difference between the level of physical fitness between the students of junior high school located in mountainous area and those of junior high school located in the coastal area. Keywords : Physical Fitness, Mountainous Area, Coastal Area.